“Like, Pasta, Pizza and Stuff” – New Trends in Online Food Discourse - Diemer, Stefan; Brunner, Marie-Louise; Schmidt, Selina (Cuizine)

(untitled) (McGill University Library, 2014)
This paper examines two examples of online food discourse to illustrate how the medium changes parameters established in print recipes: food blogs for written and Skype talks for oral computer-mediated discourse about food. The language of food blogs will be analysed with the help of examples from the Food Blog Corpus (Diemer and Frobenius 2011), compiled at Saarland University, Saarbrücken, Germany. This corpus includes 100 blog posts in total from The Times Online. Skype conversations about food between non-native speakers of English are taken from CASE, the Corpus of Academic Spoken English (Diemer et al. forthcoming), also compiled at Saarland University, Saarbrücken, Germany. For the purpose of this analysis, a subcorpus of food-related conversations was extracted, containing seven conversations (5.5h) between 14 German and Italian participants in total. The two corpora were examined in terms of contextualisation (reference to place, time, and personal background), register (audience, and linguistic features), as well as personal opinions and lifestyle comments. The paper suggests that both discourse types make use of the multimodal online environment and add evaluative content, for example integrating positively connoted terms to describe food-related issues. The paper also illustrates possible trends towards an increasing inclusion of non-expert language features, such as vagueness and a reduction of presuppositions, and of cultural and personal references, integrating individual background information.